Dynamic/quasi-static stab-resistance and mechanical properties of soft body armour composites constructed from Kevlar fabrics and shear thickening fluids. Issue 63 (15th August 2017) - Qin, Jianbin; Zhang, Guangcheng; Zhou, Lisheng; Li, Jiantong; Shi, Xuetao
Abstract : Soft body armour composites were constructed by combining Kevlar fabrics with different quantities of shear thickening fluid (STF). Abstract : Soft body armour composites were constructed by combining Kevlar fabrics with different quantities of shear thickening fluid (STF). In particular, the quantity of the added STF and the mechanical properties of these composites were systemically explored. The dynamic and quasi-static knife-stabbing resistance and the quasi-static mechanical properties of these composites were both significantly enhanced in comparison to those of neat Kevlar fabric. The composites were much lighter, thinner and more flexible than the neat Kevlar fabric and, with an optimal quantity of added STF, could not even be penetrated. However, the dynamic knife-stabbing resistance of the fabric became poor when the amount of added STF was higher than 100 wt%. The tensile strength of the composites could be increased from 40% to 80% and the tearing strength could be increased by nearly eight times that of the neat Kevlar fabric by increasing the concentration of added STF. Yarn pull-out testing suggested that the triggered shear thickening contributed to the increase of the friction between yarns or filaments, resulting in improvements in the dynamic and quasi-static properties of these composites. Moreover, these composites are suitable for use as soft body armour materials due to their good adaptability to high and low speeds conditions.